2021
DOI: 10.24959/ophcj.21.231947
|View full text |Cite
|
Sign up to set email alerts
|

The study of the effect of ethyl alcohol concentrations on the antioxidant activity of ascorbic acid solutions

Abstract: Much attention is currently paid to the study of the antioxidant properties of various objects – individual antioxidants, dietary supplements, medicines, liquid plant extracts. Antioxidant medicines are widely used as the main or additional correction agents in the treatment of a number of diseases. Therefore, the study and development of procedures for determining the antioxidant activity is a prospective task for today. Aim. To determine the contribution of different concentrations of ethanol to the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In our opinion, the results of their study on the determination of the AOA of the extract may not be reliable as they did not take into account the AOA of ethyl alcohol. In our previous studies [18], it was found that ethyl alcohol contributes to overall level of antioxidant activity.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In our opinion, the results of their study on the determination of the AOA of the extract may not be reliable as they did not take into account the AOA of ethyl alcohol. In our previous studies [18], it was found that ethyl alcohol contributes to overall level of antioxidant activity.…”
Section: Introductionmentioning
confidence: 87%
“…The shift of potential is explained by the change of ratio of o of the mediator system. The following equation was used to calcu mmol-eqv./mres dry weight [18,23]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant activity. The antioxidant activity was assessed using the potentiometric method [14,15,16]. Antioxidant activity was calculated according to the following equation and expressed as mmol-equiv./L .…”
Section: Methodsmentioning
confidence: 99%
“…where A -is the absorbance of the solution analyzed; 188 -is the specific absorption of chlorogenic acid; V -is the volume of the extract, mL; K dil -is the dilution coefficient. The antioxidant activity of the extracts was measured by the potentiometric method [12] calculated according to the following equation, and expressed as mmol-equiv m dry res.…”
Section: Preparation Of the Standard Solutionsmentioning
confidence: 99%